2002
DOI: 10.1590/s0100-736x2002000400004
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologia das helmintoses pulmonares e gastrintestinais de bezerros em região de baixada do Estado do Rio de Janeiro

Abstract: Foi estudada a epidemiologia das helmintoses pulmonares e gastrintestinais em bezerros mestiços (Zebu x Holandês) mantidos em regime de pastoreio permanente em região de baixada, correspondente ao clima Aw, no Estado do Rio de Janeiro. Os animais tinham entre 6 e 9 meses de idade, e o experimento teve duração de 24 meses. Os animais eram portadores de infecção natural por diversas espécies de helmintos e o trabalho baseou-se na contagem de ovos por grama de fezes e necropsias de pelo menos quatro animais a cad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
(6 reference statements)
2
4
0
1
Order By: Relevance
“…The low parasitic loads observed in the present study may be attributed to use of a rotational grazing system, as observed by Dimander et al (2003). Pimentel Neto and Fonseca (2002) stated that in managing calves from three months of age onwards, it is necessary to be aware of worms, which can affect these animals up to the age of two years. The animals should receive special attention during this phase.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The low parasitic loads observed in the present study may be attributed to use of a rotational grazing system, as observed by Dimander et al (2003). Pimentel Neto and Fonseca (2002) stated that in managing calves from three months of age onwards, it is necessary to be aware of worms, which can affect these animals up to the age of two years. The animals should receive special attention during this phase.…”
Section: Discussionsupporting
confidence: 65%
“…Pimentel Neto and Fonseca (2002) studied populations of gastrointestinal helminths in calves and cows in the Municipality of Seropédica, RJ, over a number of years, and observed that Haemonchus predominated, followed by Trichostrongylus. The predominance of the genus Trichostrongylus during the dry season is related to the higher resistance of this worm to the environment during the more hostile seasons, which facilitates both survival and reinfection.…”
Section: Discussionmentioning
confidence: 99%
“…in mixed infections, and this was a highly frequent species in the present study. Furthermore, according to Pimentel Neto and Fonseca (2002), establishment of parasites in calves is related to the animal's age, the helminth genus and the rearing location (management, regional climate, etc). Therefore, it is likely that some of these factors that were not evaluated factors in the present study may separately or in association have interfered with the results observed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, although data on parasites of domestic mammals are quite common (Nichol et al, 1981;Farias et al, 1995;Pimentel Neto & Fonseca, 2002;Serra et al, 2003), studies about helminth parasites preying on arboreal rodents are rare due to the general lack of specific research on host-parasite relationships (Summa, pers. comm.).…”
mentioning
confidence: 99%